Clinical use of multislice spiral computed tomography in 210 highly preselected patients: experience with 4 and 16 slice technology. Issue 11 (10th March 2005) - Beck, T; Burgstahler, C; Kuettner, A; Kopp, A F; Heuschmid, M; Claussen, C D; Schroeder, S
Abstract : Objective: To report an initial experience with multislice spiral computed tomography (MSCT) coronary imaging, as well as differences in diagnostic accuracy between 4 slice and 16 slice MSCT technology. Methods and results: 210 patients underwent MSCT coronary angiography (4 slices, n  =  120; 16 slices, n  =  90; suspicion of coronary artery disease, n  =  158; suspicion of restenosis, n  =  52). Recommendations for further diagnostic tests were based on the MSCT results. Patients were interviewed by telephone after a mean (SD) of 449 (169) days to evaluate their further clinical course. MSCT detected significant lesions in 90 of 210 (43%) patients and invasive coronary angiography (ICA) was recommended. MSCT excluded significant lesions in 120 of 210 (57%) patients. ICA was actually performed in 44 of 210 (21%) patients (corresponding results, 27 of 44 (61%); false positive, 11 of 44 (25%); false negative, 6 of 44 (14%)). No significant differences were found between 4 and 16 slice imaging. No major cardiac event occurred during follow up. Conclusions: MSCT was found to be useful to evaluate the need for invasive diagnostic procedures. However, the false negative results underline that further improvements of image quality are required before MSCT can replace ICA in carefully selected patients.